The BRC global standard for food safety : a guide to a successful audit - Kill, R. C. (Wiley-Blackwell, 2012)
This book will offer companies in the food industry a comprehensive guide to preparing for a British Retail Consortium Standard evaluation (Issue 6). It will enable them to ensure that the correct systems are in place to achieve the Standard, and also that they present themselves in the best possible light during the audit process. It will also recommend the correct steps to take following evaluation and how to correct non-conformities. The book will be of interest not only to suppliers who are seeking certification for the first time but also to those already in the scheme, and are seeking to.
Keywords: Food industry and trade -- Standards -- Great Britain.; Food industry and trade -- Standards.; elektronické knihy; electronic books